Comparison of gut microflora of donkeys in high and low altitude areas - Guo, Rong; Zhang, Shuer; Chen, Jianxing; Shen, Wei; Zhang, Guoliang; Wang, Junjie; Zhang, Fali; Pan, Qingjie; Xie, Taifeng; Ai, Deqiang; Dong, Jianbao; Suo, Jiajia; et al. (Frontiers in Microbiology, 2022)
Donkeys’ gut microbe is critical for their health and adaptation to the environment. Little research has been conducted on the donkey gut microbiome compared with other domestic animals. The Tibetan Plateau is an extreme environment. In this study, 6 Qinghai donkeys (QH) from the Tibetan Plateau and 6 Dezhou donkeys (DZ) were investigated, and the contents of 4 parts—stomach, small intestine, cecum, and rectum—were collected. 16S rRNA sequencing and metagenomic sequencing were used to analyze the composition and diversity of gut microbial communities in donkeys. The results showed that the flora diversity and richness of the hindgut were significantly higher than those of the foregut (p < 0.01), with no sex differences, and the community structure and composition of the same or adjacent regions (stomach, small intestine, cecum, and rectum) were similar. Besides, the flora diversity and richness of QH on the Tibetan Plateau were significantly higher than those of DZ (p < 0.05). The major pathways associated with QH were signal transduction mechanisms and carbohydrate transport and metabolism, and Bacteroidales were the major contributors to these functions. Our study provides novel insights into the contribution of microbiomes to the adaptive evolution of donkeys.